A Global Survey of Infection Control and Mitigation Measures for Combating the Transmission of COVID-19 Pandemic in Buildings Under Facilities Management Services - Sarvari, Hadi; Chen, Zhen; Chan, Daniel W. M.; Lester, Ellyn A.; Yahaya, Nordin; Nassereddine, Hala; Lotfata, Aynaz (Frontiers in Built Environment, 2022)
Facilities management along with health care are two important aspects in controlling the spread of infectious diseases with regard to controlling the outbreak of COVID-19. Hence, with the increasing outbreak of COVID-19, the importance of examining the relationship between the built environment and the outbreak of infectious diseases has become more significant. The aim of the research described in this article is to discover effective control and mitigation measures to prevent the transmission of COVID-19 in the built environment. This study seeks to answer the question of how the facilities management industry can help reduce the transmission of coronavirus. For this purpose, the online survey questionnaire was distributed internationally from 8 April to 25 July, 2020 to collect data. The collected data were analyzed by SPSS software. Various methods for the prevention and control of infectious diseases transmission are evaluated through this questionnaire-based survey with regard to their effectiveness for the healthy and safe built environment. These methods were categorized into three groups, including training protocols, operation and maintenance, and design and construction. The results show that all methods have a positive effect in all types of buildings. These methods have an equal effect in low-risk buildings, while for high and very high-risk buildings, training protocols and design and construction measures have the greatest impact. In addition, training protocols and the measures in operation and maintenance will have the greatest effect, in medium-risk buildings, respectively. The results would enable decision-makers to make more rational decisions in relation to controlling the outbreak of COVID-19 in all types of buildings.